Epidemiological issues in diabetic retinopathy. - Scanlon, P; Aldington, S; Stratton, I (2013)
There is currently an epidemic of diabetes in the world, principally type 2 diabetes that is linked to changing lifestyle, obesity, and increasing age of the population. Latest estimates from the International Diabetes Federation (IDF) forecasts a rise from 366 million people worldwide to 552 million by 2030. Type 1 diabetes is more common in the Northern hemisphere with the highest rates in Finland and there is evidence of a rise in some central European countries, particularly in the younger children under 5 years of age. Modifiable risk factors for progression of diabetic retinopathy (DR) are blood glucose, blood pressure, serum lipids, and smoking. Nonmodifiable risk factors are duration, age, genetic predisposition, and ethnicity. Other risk factors are pregnancy, microaneurysm count in an eye, microaneurysm formation rate, and the presence of any DR in the second eye. DR, macular edema (ME), and proliferative DR (PDR) develop with increased duration of diabetes and the rates are dependent on the above risk factors. In one study of type 1 diabetes, the median individual risk for the development of early retinal changes was 9.1 years of diabetes duration. Another study reported the 25 year incidence of proliferative retinopathy among population-based cohort of type 1 patients with diabetes was 42.9%. In recent years, people with diabetes have lower rates of progression than historically to PDR and severe visual loss, which may reflect better control of glucose, blood pressure, and serum lipids, and earlier diagnosis.